Carbon formation in catalytic steam reforming of natural gas with SOFC anode off-gas. (21st January 2015) - Kihlman, Johanna; Sucipto, Juli; Kaisalo, Noora; Simell, Pekka; Lehtonen, Juha
Abstract: Natural gas was reformed with anode off-gas of a solid oxide fuel cell (SOFC) in a laboratory reactor using model gases. Nickel and precious metal catalysts were tested at 650 °C and 700 °C inlet temperature. The oxygen to carbon (O/C) molar ratio of the inlet gas was varied between 0.3 and 2.0 to find out the limit O/C ratio for carbon formation. Two natural gas compositions were used: low purity Danish gas and high purity Russian gas. The experimental limit was found to be 0.9–1.25 for nickel catalyst and 0.5–0.75 for precious metal catalyst. The limit was higher with Danish gas than with Russian gas in the experiments with nickel catalyst but this effect was not observed with the precious metal catalyst. A good correlation between experimental results and thermodynamic calculations was found using the principle of actual gas: the calculations estimated the O/C limit ratio for nickel at 1.0 and for precious metal catalyst between 0.5 and 0.7. Highlights: Carbon formation in methane reforming with anode off-gas was studied. Limit O/C molar ratios for carbon formation was obtained for two catalysts. Precious metal catalyst had low O/C limit ratio of 0.5–075. Nickel catalyst had O/C limit ratio between 0.9 and 1.25. The O/C limit ratios correlated well with calculations by principle of actual gas.